التكييف الفقهي وأثره في اختلاف الفقهاء - ماني سعادة, حسين (جامعة الوادي University of Eloued, 2016)
البحث يُعرِّفُ بالتّكييف الفقهي، باعتباره أحدَ أسباب اختلاف الفقهاء قديماً وحديثاً، مبرزاً أهميته ومسالكه، وأثره في الاختلاف داخل المذهب الواحد، كاختلاف فقهاء المذهب المالكي في التّكييف الفقهي لكراء السُّفن، وأثره أيضاً في اختلاف المذاهب الفقهيّة كاختلافهم في التّكييف الفقهي لمن أكل أو شرب عامداً في نهار رمضان، وكذلك أثره في اختلاف الفقهاء المعاصرين كاختلافهم في التّكييف الفقهي لخطاب الضّمان. ABSTRACT: This work defines what is called the jurisprudential adaptation as being one of the reasons behind scholars' controversy both in the past and in modern times. Highlighting its importance, methods as well as its impact on the differences in the same doctrine, like the controversy between among the Malikite school's . The same thing regarding the eatin and drinking in the day of Ramadan, and other contemporary. As well as the dissimilarity in the emerging themes, such as of the letter of guarantee.
Jurisprudence Adaptation And Its Impact On The Scholars Diversities
Keywords: الاختلاف – الفقه- المذاهب – البحث; Adaptation – being – scholars – controversy